An enzyme common to histidine and aromatic amino acid biosynthesis in Bacillus subtilis. - Nester, E W (1976)
Two transaminases exist for tyrosine and phenylalanine synthesis in Bacillus subtilis. One enzyme is also responsible for the transamination of imidazole acetol phosphate to histidinol phosphate, an obligatory reaction in the synthesis of histidine. The gene involved in the synthesis of this enzyme lies in the middle of a cluster of genes, all of which are concerned with the synthesis of the aromatic amino acids. The other gene has not yet been mapped. Mutants have been isolated that lack one or the other enzyme activity. These mutants are prototrophic for tyrosine and phenylalanine. However, both classes of mutants are more sensitive than the wild-type strain to the phenylalanine analogue, fluorophenylalanine, suggesting that each of these mutants synthesizes less phenylalanine than does the wild-type strain. The two enzymes can be separated from one another by ion-exchange chromatography and glycerol-gradient centrifugation. The significance of the observation that an enzyme of histidine synthesis also plays a role in the synthesis of the aromatic acids is considered in light of cross-pathways regulation between the two pathways.